Institutional Quality and Financial Development: Evidence from Developing and Emerging Economies. Issue 4 (August 2022) - Khan, Hayat; Khan, Sher; Zuojun, Fan
Using a panel data set of 189 countries by employing dynamic models OLS, fixed effect, random effect and generalized method of moments (GMM) estimators. The study revisits the relationship between institutional quality and financial development in developing and emerging countries. This study is ever the first comprehensive and wide-ranging that categorizes the countries into developing and emerging countries using multiple dynamic approaches. Experimental findings of the study are based on GMM, which indicates that better institutions are important for financial development, specifically political stability, control of corruption and regulatory quality positively affect financial development in the global panel of the study. Rule of law negatively affects financial development, which reveals that in most of the global countries, the rule of law is very feeble. Control of corruption index is positively effecting financial development in emerging and global panel which indicates that most of the countries have reduced corruption to low level. The current study also found that emerging countries have reduced corruption, but other institutional indicators are found to be insignificant. The overall result concludes that good quality institutions are the main drivers of financial development and it stimulates financial development. The present study suggests that developing and emerging countries should focus to improve the institutional quality by re-examining the rules of law, government effectiveness and voice accountability institutional factors to make it better.